Quo Vadis I'jaz 'Ilmi : Karakteristik dan Persinggungannya dengan Fakta Sains - Khoiri, Shohib; Sulthoni, Akhmad (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2024)
This study aims to examine the development of the study of i'jaz ilmi and the signs that must be considered so that the study of i'jaz ilmi does not deviate. The focus of this study consists of several important points, namely the development of tafsir ilmi and its characteristics, a critical study of the definition of i'jaz ilmi and tafsir ilmi that developed in the community, and the signs in the study of i'jaz ilmi so that no mistakes occur. This research uses qualitative-descriptive-analytic methodology. Based on the research, it is found that: First, Despite the pros and cons among scholars, i'jaz and tafsir ilmi is one of the studies of the Qur'an that is widely discussed by scholars, this is evident from the emergence of several works related to it, including in Indonesia. Second, some scholars argue that i'jaz ilmi and tafsir ilmi are two different things, this difference lies in the potential error that will occur. I'jaz ilmi is considered a definite truth while tafsir ilmi has the possibility of error. However, in practice i'jaz ilmi also has the possibility of being wrong as long as there is no explicit signal that shows the relationship of a verse with scientific facts, meaning that if the condition is so then i'jaz ilmi and tafsir ilmi are only based on conjectures that have the possibility of being wrong. Third, to minimize the occurrence of errors, it is necessary to pay attention to some of the signs in the study, namely the use of sentences that can be used in the study.